Brazil : Assessment of the Bolsa Escola Programs - World Bank (Washington, DC, 2013)
The report assesses the "Bolsa Escola" programs in Brazil, which are poverty-targeted social assistance programs, that provide cash grants to poor families with school-age children between the ages of seven to fourteen. These programs aim at increasing educational attainment, to reduce current, and future poverty, as well as child labor, and, implicitly, to act as a partial safety net. The rationale for these programs should be considered in the context of the current picture of poverty in the country, where the strongest correlates of current poverty is low education. The programs under discussion have widespread support, and fit well into Brazil's larger social protection, and poverty reduction strategies, because they explicitly target the poor, with sound criteria for beneficiary selection, based on a score system, comprising living standards indicators. Preliminary evidence suggests the programs have been reasonably successful in targeting, and points to improvements in education, and poverty outcomes, although evidence on child labor reduction, is inconclusive. The need to reach the "non-covered" population is suggested, as well as the level of cash transfers needs to be determined carefully, while the "Bolsa Escola" programs should not be seen by local governments, as substitutes for investments in schools. Probably the biggest consideration in the successful expansion of these programs, is their fiscal affordability, bearing in mind the programs protect the structurally poor during crisis, equipping the next generation with risk reducing human capital.